Teacher Self-Efficacy and Engagement in Professional Development - Pramudya, Gitarani; Mardikaningsih, Rahayu (Journal of Social Science Studies, 2021)
Teachers’ self-efficacy determines their engagement in professional development programs. This study presents a synthesis of how teachers’ efficacy in personal capacity influence motivation, persistence and active participation in sustainable training. Through a thematic analysis of Bandura’s theory of self-efficacy, this study highlights the main sources of efficacy, namely direct experience, vicarious learning, verbal feedback, and affective states and the mechanisms of their application in education. The findings show that teachers with high efficacy are more responsive to pedagogical innovations, open to feedback and quicker to implement new strategies in the classroom. In contrast, low self-efficacy inhibits participation and reduces the effectiveness of training programs. Practical implications include recommendations for training designs that reinforce successful experiences, sustainable mentoring and a culture of organizational support. The results of this research provide a foundation for education policymakers and practitioners in designing professional development interventions oriented towards increasing teachers’ self-efficacy.